Overview of management of children with COVID-19 - Dyah Kanya Wati; Arya Krisna Manggala (The Korean Pediatric Society, 2020)
The widespread and contagious coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 has become a burden in the global health domain. The subsequent discovery of the virus features and pathogenesis, and prompt and adequate management are still lacking and remain inconclusive. Children usually present milder symptoms than adults, and management focuses on providing symptomatic and respiratory supports. Several treatment modalities, including the utilization of mechanical ventilation (MV), antivirals, immune-modulating drugs, or other agents, may present promising results in reducing the symptoms of COVID-19, particularly in severe cases. Although no randomized clinical trials have been published to date, it is interesting to explore potential modalities for treating COVID-19 in children, based on review articles, case reports, and recent guidelines.